Exposure to climate risks and youth engagement with climate change - Blessman, Max; Hurst, Kristin F.; Nelson, Christopher J.; Toedte, Ross J.; Tyrell, Jennifer D. (Frontiers in Climate, 2025)
Effectively mitigating and adapting to the effects of climate change over the coming decades will require the active engagement of today’s youth. This research adds to a growing body of work focused on youth climate change engagement by testing whether physical exposure to climate risks influences middle school and high school students’ intentions to engage in pro-climate behaviors above and beyond several previously identified social and psychological variables. A total of 222 middle and high school students across 11 states were surveyed to measure cognitive, social, and demographic factors known to influence pro-climate behavior. We combined this survey data with data from a national assessment of climate risks and conducted a hierarchical regression model predicting intentions to engage in pro-climate behaviors. Physical exposure to climate risks was not a significant predictor in our model. Rather, we found that the only significant predictors of behavioral intentions were perceived risks of climate change and frequency of discussions with friends and family. Since the size and geographic distribution of our sample was limited, future research is needed to build on these findings and the role youth may play in mitigating climate change.